2021
DOI: 10.1002/chem.202101607
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer Metal‐Organic Framework Containing Redox‐Active TTF/NDI Units for Highly Efficient Near‐Infrared Photothermal Conversion

Abstract: Metal-organic frameworks (MOFs), as a class of new inorganic-organic hybrid crystal materials, could have important applications in near-infrared (NIR) photothermal conversion. Herein, a new charge-transfer MOF (Co-MOF) with mixed ligands of H 4 TTFTB and bpmNDI incorporating redox-active tetrathiafulvalene/naphthalene diimide (TTF/ NDI) units into one system is reported. Due to the presence of TTF/NDI oxidative and reductive couples, stable radicals can be observed in the MOF. In addition, charge transfer fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…In addition to the optical and electrical properties described above, D–A MOFs with CT or ET interaction may exhibit properties such as magnetism 67 and photothermal conversion. 68 There are plenty of reports with cogent results, simultaneously, exploring the additional properties. Fukunaga et al constructed a pillared layer D–A system, which was composed of [FeCp* 2 ] (decamethylferrocene) as the interlayer pillar and the 2D D 2 A type polymer formed by TCNQ (tetracyanoquinodimethane) and ruthenium (Ru) as a layer.…”
Section: Properties Of D–a Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the optical and electrical properties described above, D–A MOFs with CT or ET interaction may exhibit properties such as magnetism 67 and photothermal conversion. 68 There are plenty of reports with cogent results, simultaneously, exploring the additional properties. Fukunaga et al constructed a pillared layer D–A system, which was composed of [FeCp* 2 ] (decamethylferrocene) as the interlayer pillar and the 2D D 2 A type polymer formed by TCNQ (tetracyanoquinodimethane) and ruthenium (Ru) as a layer.…”
Section: Properties Of D–a Mofsmentioning
confidence: 99%
“…Several relative works demonstrated that D–A MOFs are excellent candidates for photothermal imaging and therapy, which discloses the potential applied value. Zuo et al reported a D–A charge transfer MOF, 68 which consisted of tetrathiafulvalene tetrabenzoate (H 4 TTFTB) and N , N ′-bis(4-pridylmethyl)-1,4,5,8-naphthalene diimide (BPMNDI) mixed ligands. Both ligands feature strong redox properties (Fig.…”
Section: Properties Of D–a Mofsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), one class of hybrid crystalline materials consisting of organic linkers and metal nodes/clusters, have attracted much attention in recent decades due to their controllable structures, modular nature, and potential applications in molecule separation, sensing, , luminescence, , catalysis, , energy-related fields, , etc. Recently, some MOFs have been applied as carriers for photothermal material encapsulation to achieve integration and synergistic enhancements, but only a few MOFs with near-infrared photothermal conversion capability have been reported. Thus, studying the design and synthesis of MOFs with near-infrared photothermal conversion behavior is worthwhile.…”
Section: Introductionmentioning
confidence: 99%
“…Both of them have reversible multistep redox activity. In 2021, we reported one two-dimensional (2D) MOF, Co-MOF , constructed from organic ligands TTF and NDI, which showed good near-infrared photothermal conversion performance. In this material, the near-infrared photothermal conversion property resulted from interlamination π···π interactions between TTF and NDI units . On the basis of this previous work, we chose the same TTF ligand and the semirigid NDI ligand to construct a new MOF.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Yin and co-workers reported the first example of a MOF as a NIR photothermal material containing stable perylenediimide radical anions. 15 Xu et al prepared a viologencontaining coordination polymer, 16 and Zuo's group constructed a Co-MOF containing redox active tetrathiafulvalene/ naphthalene diimide units, 17 and both exhibited remarkable NIR photothermal effects. However, most reports of MOFs are on the bulk crystals with absorption in the visible or NIR-I windows.…”
mentioning
confidence: 99%